2013
DOI: 10.1097/spv.0b013e31827bfd7b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pelvic Floor Symptoms and Sexual Function in Primiparous Women Who Underwent Operative Vaginal Delivery Versus Cesarean Delivery for Second-Stage Arrest

Abstract: Objectives This study aimed to compare the prevalence and severity of pelvic floor symptoms and sexual function at 1 year postpartum in women who underwent either operative vaginal delivery (OVD) or cesarean delivery (CD) for second-stage arrest. Methods In this cohort study, women with second-stage arrest in their first pregnancy who delivered between January 2009 and May 2011 at 2 different institutions were identified by an obstetric database using International Classification of Diseases, Ninth Revision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
1
20
1
2
Order By: Relevance
“…Accordingly, as opposed to the popular belief, it was found that the damage to the pelvic support tissue might occur not only in the second stage, but also in the first stage of labor [33]. In another study along the same lines, CD, which was performed after a pause in the second stage of labor in primiparous women, has no protective effect in terms of the PFD development [34]. Previous studies indicate that there is not sufficient evidence to recommend widespread use of elective CD for the prevention of PFD [35].…”
Section: Effect Of Normal Delivery and CD On Pfdmentioning
confidence: 88%
“…Accordingly, as opposed to the popular belief, it was found that the damage to the pelvic support tissue might occur not only in the second stage, but also in the first stage of labor [33]. In another study along the same lines, CD, which was performed after a pause in the second stage of labor in primiparous women, has no protective effect in terms of the PFD development [34]. Previous studies indicate that there is not sufficient evidence to recommend widespread use of elective CD for the prevention of PFD [35].…”
Section: Effect Of Normal Delivery and CD On Pfdmentioning
confidence: 88%
“…Symptoms associated with pelvic floor trauma include pain, dyspareunia, and urinary and bowel incontinence. [94][95][96][97][98][99][100] However, a longitudinal prospective cohort study nested with a two-centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic floor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum. 101 This suggests that much of the pelvic floor morbidity reported by women in the weeks and months after an assisted vaginal birth may not be causally related to the procedure.…”
Section: Evidence Level 1++mentioning
confidence: 99%
“…Vacuum and forceps birth are associated with a higher incidence of episiotomy, pelvic floor tearing, levator ani avulsion and obstetric anal sphincter injury (OASI) than spontaneous vaginal birth. Symptoms associated with pelvic floor trauma include pain, dyspareunia, and urinary and bowel incontinence . However, a longitudinal prospective cohort study nested with a two‐centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic floor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum .…”
Section: Performing Assisted Vaginal Birthmentioning
confidence: 99%
“…OVD has not clearly been reported as an independent risk factor for alteration of sexual function [13,15,17,18]. Recently, Barbara et al [19] reported that OVD (n = 45) might be associated with poorer female sexual functioning, and specifically poorer scores on arousal, lubrication, orgasm, and global sexual functioning compared with a cesarean section group (n = 92) and lower orgasm scores compared with a spontaneous vaginal delivery group (n = 132) [19].…”
Section: Introductionmentioning
confidence: 99%